2004
DOI: 10.1002/jsfa.1855
|View full text |Cite
|
Sign up to set email alerts
|

Papain hydrolysates of casein: molecular weight profile and encapsulation in lipospheres

Abstract: Some reaction parameters were tested in the hydrolysis of casein by papain, in order to prepare hydrolysates with high oligopeptide contents, for either dietetic or pharmaceutical purposes. Five casein hydrolysates were prepared and then fractionated by size-exclusion HPLC. The rapid correct fraction area method was used for quantifying peptides and free amino acids. Among the five reaction conditions tested, three produced similar peptide profiles. However, the use of a temperature of 37 • C and an E:S ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 39 publications
(56 reference statements)
3
15
0
1
Order By: Relevance
“…This result was similar to that obtained by Barbosa et al (2004), Morais et al (2003), and Morais et al (2005), who found that the encapsulation of casein hydrolysates in liposomes and lipospheres caused bitterness reduction. However, spray drying is a low cost and simple process and soy protein is an abundant, inexpensive and renewable natural material.…”
Section: Sensory Evaluationsupporting
confidence: 94%
See 1 more Smart Citation
“…This result was similar to that obtained by Barbosa et al (2004), Morais et al (2003), and Morais et al (2005), who found that the encapsulation of casein hydrolysates in liposomes and lipospheres caused bitterness reduction. However, spray drying is a low cost and simple process and soy protein is an abundant, inexpensive and renewable natural material.…”
Section: Sensory Evaluationsupporting
confidence: 94%
“…Some authors have encapsulated casein hydrolysates in liposomes [Morais et al, 2003;Morais, De Marco, Oliveira, & Silvestre, 2005] and lipospheres (Barbosa et al, 2004) and they also reported the decrease in hydrophobicity of casein hydrolysates after microencapsulation.…”
Section: Microcapsules Characterizationmentioning
confidence: 97%
“…Therefore, using this particle formulation, casein hydrolysate was incorporated into the dispersions, resulting in an encapsulation efficiency of 73.9±4.5 %. This value was considered extremely satisfactory and was comparable to the results obtained by Barbosa et al (2004), who also worked with the encapsulation of casein hydrolysates in lipid microparticles of stearic acid. However, when comparing the size distributions of empty and casein hydrolysate-loaded LM as depicted in Figure 5, it is clear that the incorporation of casein hydrolysate changed the characteristics of the dispersions dramatically.…”
Section: Lipid Microparticles: Production Characterization and Encapsupporting
confidence: 87%
“…Em diversos estudos o perfil peptídico de hidrolisados enzimáticos de diferentes fontes protéicas (caseína, soro de leite e leite em pó) foi determinado a fim de se avaliar a composição em peptídeos e aminoácidos livres (Morato et al, 2000;Carreira et al, 2004;Lopes et al, 2005;Morais et al, 2005;Soares et al, 2006;Barbosa et al, 2004;De Marco et al, 2005;Silva et al, 2005;Delvivo et al, 2006).…”
Section: Introductionunclassified